Lola Mora in Tucumán: Personal Costs and Benefits of Creating Public Art, 1890-1904 - Vignoli, Marcela (2022)
rom a traditional perspective, women who have triumphed in the arts, literature, or science have been seen as an anomaly or “exceptional women” by historians. In 1895, only a third of girls under 14 could read in the small provincial town of Tucuman, in northern Argentina. However, Lola Mora displayed her sculptures in her first exhibitions in the same year. Her career as a sculptor was legitimized and recognized in her hometown Argentina, after spending years in Europe developing her talent. Her career as an artist has historically been seen as a distinct rarity, and few people have attempted to provide an explanation or contextualization for her success as an artist at the turn of the 20th century. In this article, I propose an analysis of the methods that Lola Mora used to legitimize her art and establish herself professionally. I would like to draw attention to Lola Mora’s conscious decision to contradict the contemporary ideals of patriotism and politics as themes in her art; her sculptures were physical manifestations of her feelings on the contentious aforementioned subjects. Lola Mora realigned her focus on the intricacies of provincial and national politics during the 1890s, but she did not abandon her art. Her career has been interpreted as a radical deviation from the lives that women conducted publicly in the 20th century.